Disabilities Student’s Perspective in a Hybrid Learning During Covid-19 Pandemic at UIN Sunan Kalijaga Yogyakarta - Fithriya, Dwi Nur Laela; Dewi, Maya Sandra Rosita; Ardhana, Bagas Pramudya (Universitas Negeri Padang, 2024)
Indonesia's education world is experiencing significant changes due to the ongoing COVID-19 pandemic. This change can be seen from the enactment of online teaching and learning activities. In the even semester of the 2021/2021 Academic Year, the COVID-19 pandemic subsided a little. This also impacts the policy of implementing learning activities, especially in the higher education environment. Responding to the Indonesian government's decision regarding the Implementation of Face-to-Face Learning for the 2021/2022 Academic Year, UIN Sunan Kalijaga also organizes lecture activities in which each lecturer can hold offline lectures together with online lectures (in the network). Learning with online and offline models at UIN SUKA is adapted to existing conditions in the field, especially for students with disabilities. This research uses structural functional theory (AGIL). The results of this study explain that students with disabilities can attend hybrid lectures even with all the limitations they have. It takes help and assistance from related parties to help run Hybrid Learning, especially for students with disabilities.